Linear circuit analysis - Chi, Kong Tse (Addison-Wesley, 1998)
A concise but comprehensive guide to circuit analysis techniques which demonstrates some alternative methods for solving circuit problems. Throughout, the author provides detailed, practical descriptions of procedures for PSpice analysis